FACTORS FOR IMPROVING THE EFFICIENCY OF ECONOMIC SECTORS IN IMPROVING THE EDUCATION SYSTEM OF UZBEKISTAN - Yuldasheva Diloro Asqaraliyevna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This study examines the relationship between the education system in Uzbekistan and the performance of key sectors of the economy, highlighting the potential of education reforms to increase productivity, innovation, and overall economic growth. As Uzbekistan seeks to modernize its economy, aligning educational outcomes with sectoral needs is increasingly important. The study examines how improvements in vocational education, STEM (science, technology, engineering, and mathematics) education, and industry-academia collaboration can address skills gaps, foster technological progress, and enhance the competitiveness of Uzbekistan’s agriculture, manufacturing, information technology (IT), and energy sectors.